Morphometric And Meristic Variations of Threadfin Breams Fish (Family: Nemipteridae) in Kupang: A Comparative Study from Oeba Fish Landing Site and Oesapa Fish Market - Umbu Domu Wora; Nenik Kholilah; Fanny Iriany Ginzel; Krisman Umbu Henggu (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro, 2025)
Threadfin Bream fish (Nemipteridae) are among the frequently landed species at the Oeba Fish Landing Site and the Oesapa Fish Market in Kupang City, East Nusa Tenggara, Indonesia. These fish are widely consumed by local communities, sold in domestic markets, and exported. This study aimed to analyze the morphometric and meristic characteristics of Threadfin Bream fish and compare the morphological variations of specimens collected from two distinct locations: TPI Oeba and Oesapa Market. The research was conducted from April to May 2023. Four species of Threadfin Bream were identified: Nemipterus japonicus, N. hexodon, N. zysron, and N. aurora. A total of 18 morphometric and 10 meristic characters were measured. The recorded total lengths were: N. japonicus (215 mm), N. hexodon (197 mm), N. zysron (247 mm), and N. aurora (242 mm). Average meristic characteristics included dorsal fin rays D.X.9, pectoral fin rays P.14, ventral fin rays V.I.5, anal fin rays A.III.7, and caudal fin rays C.20. Additional scale counts ranged as follows: pre-dorsal scales (36–41), lateral line scales (137–142), caudal peduncle scales (26–34), transverse body scales (131–169), and caudal fin height (0.8–1.3 mm). These findings contribute baseline data essential for the conservation and sustainable management of Threadfin Bream populations in the coastal waters of Kupang City.